2000
DOI: 10.1161/01.cir.102.10.1172
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cytosolic Ca 2+ Loading and Improved Cardiac Function After Cardioplegic Cold Storage of Guinea Pig Isolated Hearts

Abstract: Background-Hypothermia is cardioprotective, but it causes Ca 2ϩ loading and reduced function on rewarming. The aim was to associate changes in cytosolic Ca 2ϩ with function in intact hearts before, during, and after cold storage with or without cardioplegia (CP). Methods and Results-Guinea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…It is well known that the colder the heart during ischemia, the longer ischemia can be tolerated with minimal tissue damage (16,43). However, it is now known that hypothermia, per se, can have a deleterious effect on function with rewarming.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the colder the heart during ischemia, the longer ischemia can be tolerated with minimal tissue damage (16,43). However, it is now known that hypothermia, per se, can have a deleterious effect on function with rewarming.…”
Section: Discussionmentioning
confidence: 99%
“…Although both F 385 and F456 decline over time, time control studies showed that the F385-to-F456 ratio (F385/F456) remained stable, indicating that effective measured [Ca 2ϩ ] was unchanged (31). The F385/F456 was converted to [Ca 2ϩ ] after correcting for background autofluorescence and noncytosolic fluorescence (see APPENDIX), as has been described in detail previously (7,10,26,27,30). Developed LVP after indo 1 loading was also not significantly altered over 3 h in the absence of ischemia.…”
Section: Measurement Of Myoplasmic Free Ca 2ϩ In Intact Heartsmentioning
confidence: 96%
“…It is well known that these solutions are protective against ischemiareperfusion (I/R) dysfunction. This protection is effected by reducing the cardiac total energy consumption (Stowe et al 2000;Wang et al 2003). In previous works, we studied the energetics of a model of beating hearts (rat) perfused with cold cardioplegia (high-K + -low-Ca 2+ crystalloid at 30°C) before subjecting them to I/R.…”
Section: Introductionmentioning
confidence: 99%